Analyzing the Effect of Flux Intensification Due to Propeller Shaft and Rudder Upon the 3D Induced Magnetic Signature of Marine Vessels - Abdalla Badr; Ahmed Elserougi; Ahmed A. Hossam-Eldin (IEEE Access, 2022)
This study investigates and analyzes the effect of flux intensification due to the propeller shaft and rudder on the 3D mapped induced magnetic signature of marine vessels. The study was designed to extrapolate the 3D induced magnetic signature and to analyze the difference between signature components in two different cases: a vessel without propeller shaft or rudder and a vessel with the propeller shaft and rudder attached. Numerical modeling was conducted using full-scale vessel dimensions and finite-element analysis (FEA) modeling software. Measurements on a 1:100 properly scaled and designed physical scale model (PSM)were conducted in a magnetically clean area. To enrich the analysis, both signature components from the numerical evaluation and experimental measurements were 3D mapped. Both the scaling technique and scaling effect on magnetic signature were investigated. The signature measurements of the scaled vessel model were performed to verify the numerical model. Both the numerical and experimental results are both discussed and shown to be consistent. The extrapolated signature components revealed that the studied effect became prominent as the saliency of the 3D mapped signature components increased. Consequently, this effect increases the magnetic susceptibility of the vessel to detection or destruction. Finally, this study suggests solutions to reduce this effect.